Epistemic injustice: Power and the ethics of knowing - Fricker, Miranda (Oxford University Press, 2007)
In this exploration of new territory between ethics and epistemology, Miranda Fricker argues that there is a distinctively epistemic type of injustice, in which someone is wronged specifically in their capacity as a knower. Justice is one of the oldest and most central themes in philosophy, but in order to reveal the ethical dimension of our epistemic practices the focus must shift to injustice. Fricker adjusts the philosophical lens so that we see through to the negative space that is epistemic injustice. The book explores two different types of epistemic injustice, each driven by a form of prejudice, and from this exploration comes a positive account of two corrective ethical-intellectual virtues. The characterization of these phenomena casts light on many issues, such as social power, prejudice, virtue, and the genealogy of knowledge, and it proposes a virtue epistemological account of testimony. In this ground-breaking book, the entanglements of reason and social power are traced in a new way, to reveal the different forms of epistemic injustice and their place in the broad pattern of social injustice."--Book cover. Justice is one of the oldest and most central themes of philosophy, but sometimes we would do well to focus instead on injustice. This book argues that there is a distinctively epistemic genus of injustice, in which someone is wronged specifically in their capacity as a knower
Keywords: EDI; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; justice sociale; phi4336; premier cycle; ressource en ligne; sciences humaines; thématiques; épistémologie

Encyclopedia of sex and gender - Malti-Douglas, Fedwa (Macmillan social science library, 2007)
Les études de genre sont devenues un domaine académique majeur depuis les années 1980, offrant une lentille à travers laquelle réexaminer et réévaluer les connaissances dans tous les domaines de l'interaction et de l'activité humaines. L'Encyclopédie du sexe et du genre englobe les divers concepts de sexe et de genre qui ont émergé de l'étude critique de ces sujets dans le monde entier, ainsi que de la réimagination émergente des sciences humaines et sociales plus traditionnelles. De vastes essais théoriques abordent les questions de sexe et de genre au niveau personnel et social ; d'autres examinent les questions d'identité, de statut, de classe, d'ethnicité, de race et de nation ; de la sexualité et du corps ; et des institutions sociales et des structures de représentation - tout cela à travers le prisme du genre. Avec une perspective véritablement mondiale, les sujets des entrées individuelles incluent l'évolution des conceptions du "féminin", la famille et la masculinité, la religion, la morale, les images culturelles, la pratique médicale, la santé publique, l'économie et la société, et bien d'autres. En outre, l'ouvrage traite des influences des études de genre sur diverses disciplines universitaires, en examinant comment elles ont transformé et utilisé des méthodes et des théories qui ont évolué.
Keywords: corps; cours; cycles supérieurs; fem7000; genre; identités LGBTQIA2+; outils; ouvrages de références; ressource en ligne; sexualité; thématiques